1988
DOI: 10.1002/jmv.1890240310
|View full text |Cite
|
Sign up to set email alerts
|

Recombination in tissue culture between varicella‐zoster virus strains

Abstract: Several clinical varicella-zoster virus isolates obtained during testing of a live varicella vaccine had DNA restriction fragment patterns resembling neither vaccine nor wild-type virus [Gelb et al., J Infect. Dis. 155, 633-640, 1987]. One explanation for these isolates was recombination in vivo. To determine if such recombination is likely, two strains of varicella-zoster virus, distinguishable by restriction endonuclease fragment size differences (wild-type strain EF and the OKA vaccine strain), were grown t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

1989
1989
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 26 publications
3
31
0
Order By: Relevance
“…Although in vitro recombination of the vaccine vOka strain with a wild-type U.S. strain has been described VOL. 76, 2002 PHYLOGENY OF VARICELLA-ZOSTER VIRUS 1977 (10), this is the first evidence of recombination between strains occurring in vivo. Recombination of wild-type strains may have consequences for virulence and selection.…”
Section: Discussionmentioning
confidence: 93%
“…Although in vitro recombination of the vaccine vOka strain with a wild-type U.S. strain has been described VOL. 76, 2002 PHYLOGENY OF VARICELLA-ZOSTER VIRUS 1977 (10), this is the first evidence of recombination between strains occurring in vivo. Recombination of wild-type strains may have consequences for virulence and selection.…”
Section: Discussionmentioning
confidence: 93%
“…It has been reported that coinfection with two different strains of the same herpesvirus led to the production of recombinant viruses both in vitro and in vivo (14,20,21,25,49,51). To quantify the recombination between the two parental BoHV-1 used in the present study, MDBK cells were coinfected with both Lam gC…”
Section: Resultsmentioning
confidence: 99%
“…Recombination between different VZV strains has been described in cell culture using restriction endonuclease fragment size analysis and hybridization (9). DNA sequence and singlenucleotide polymorphism analyses have been used to detect probable recombination in several few clinical VZV isolates (30,44), and homologous recombination has also been documented in other herpesviruses.…”
Section: Discussionmentioning
confidence: 99%